Factors associated with work-private life conflict and leadership qualities among line managers of health professionals in Swiss acute and rehabilitation hospitals - a cross-sectional study - Karin A. Peter; Ruud J. G. Halfens; Sabine Hahn; Jos M. G. A. Schols (BMC, 2021)
Abstract Background The workforce shortage of health professionals is a matter of global concern. Among possible causative factors in this shortage are the incompatibility of health professionals' work with their private life, which may lead to increased stress and burnout symptoms, job dissatisfaction and a higher intention to leave the profession prematurely. Also, poor leadership qualities among direct line managers (e.g. clinic directors, leading physicians, ward managers, team leaders) have been associated with health professionals' job dissatisfaction and intention to leave in previous studies. This study therefore aimed to identify key factors associated with health professionals' work-private life conflicts and their managers' leadership quality. Methods The study is based on a cross-sectional survey in 26 Swiss acute and rehabilitation hospitals, consisting of 3398 health professionals from various disciplines. For data analysis, multilevel models (with hospitals as the second level variable) were performed for 'work-private life conflict' and 'quality of leadership', considering significant main effects (using AIC) and significant interactions (using BIC) of potential explanatory variables. Results The main findings reveal that the compatibility of health professionals' work and private life is associated with how much they can influence shift planning (possibility of exchanging shifts, B = -2.87, p < 0.01), the extent to which their individual preferences are considered (e.g. working on one specific shift only, B = 6.31, p < 0.01), number of work shifts per weekend (B = 1.38, p < 0.01) and working hours per week (B = 0.13, p < 0.01). In addition, the factors high quantitative demands (B = 0.25, p < 0.01), being required to hide their emotions (B = 0.16, p < 0.01) and poor social community support at work (B = -0.12, p < 0.01) were related to severe work-private life conflicts among health professionals. Regarding managerial leadership, health professionals perceived the leadership qualities of their direct line manager as being better if they received more social support (B = 0.61, p < 0.01) and rewards (B = 0.41, p < 0.01) at work. Conclusions The results show key components of improving the compatibility of work and private life for health professionals as well as managerial leadership qualities, and may help leaders working in acute or rehabilitation hospitals to develop appropriate interventions.